Tinjauan Bentuk Dan Motif Hias Pada Kerajinan Celengan Di Medan - Mazaya Balqis; Heri Soeprayogi (Mahesa Research Center, 2021)
This study aims to determine and describe the shape of the motifs in the works created by Rendy Handycraft. This research is a qualitative descriptive study. The subjects of this study were 3 piggy bank crafts with motifs produced by Rendy Handicraft. The shape and decorative pattern of the piggy bank were the object of this research. The data collection methods used were observation, documentation, and interviews. The data analysis used was descriptive qualitative analysis technique. Based on the results of interviews, observation and documentation, the conclusion in this study is that Rendy dominantly uses tea dregs as the main material for his painting. Not tea bags but dry tea powder/powder. Apart from good powder with a slightly coarse and smooth texture for dark colors, there are also other ingredients such as coffee powder, egg shells as well as additional ingredients as colors enhancers such as turmeric powder as a yellow dye, pine wood powder as a white dye as well as the base color and stones gravel.